Mycobacterium fortuitum abscess following breast nipple piercing. (2020) - Siddique, Nikhut; Roy, Moni; Ahmad, Sharjeel
Abstract: Mycobacterium fortuitum is a non-tuberculous rapidly growing mycobacteria (RGM). We present a case of a 30 year old female who developed a right breast subareolar abscess due to M. fortuitum four months after a nipple piercing. She failed to respond to an initial three-week course of monotherapy with trimethoprim-sulfamethoxazole despite aspiration of abscess and removal of offending nipple piercing. Our patient was successfully treated with dual antimicrobial therapy. This report also includes a brief literature review of prior reported cases caused by this organism. It is important to keep M. fortuitum and other RGM species on the differential if there is failure of resolution of abscess and infection with routine antimicrobial therapy.